Asuhan Keperawatan pada Pasien Stroke Non Hemoragik dengan Gangguan Mobilitas Fisik dengan Pemberian Mirror Therapy dan Terapi Genggam Bola Karet di Wilayah Kerja Puskesmas Lingsar - Pranita, Baiq Dindin Ade (Jurnal Sains, Teknologi dan Kesehatan, 2024)
Stroke is a disease or functional disorder of the brain in the form of nerve paralysis due to bleeding (Hemorrhagic Stroke) or blockage (Non-Hemorrhagic Stroke) which can cause a decrease in muscle strength on one side of the body that can cause disability so that therapy such as Mirror Therapy and Rubber Ball Hand-Held Therapy is needed. Applying nursing care to Non-Hemorrhagic Stroke patients with physical mobility problems through the application of Mirror Therapy and Rubber Ball handheld therapy. Mirror Therapy and Rubber Ball Hand-Held Therapy are effective for increasing muscle strength in Non-Hemorrhagic Stroke patients. In Mr. R, the value of muscle strength before the intervention of Mirror Therapy was 6 kg, and in Mr. A the value of muscle strength before the intervention of Handheld Ball Therapy was 2 kg. After evaluation for 7 days, it was found that the muscle strength value in Mr. R was 10.7 kg and in Mr. A was 8.3 kg. Mirror Therapy and Rubber Ball Hand-Held Therapy are effective for increasing muscle strength in Non-Hemorrhagic Stroke patients. It is expected to apply Mirror Therapy and Rubber Ball Hand- Held Therapy to Non-Hemorrhagic Stroke patients to overcome the problem of impaired physical mobility.